1969
DOI: 10.1002/anie.196904011
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Rare Sugars

Abstract: The use of new oxidation reagents, such as the Pfitzner‐Moffatt reagent, dimethyl sulfoxide‐acid anhydrides, and ruthenium tetroxide, has significantly improved the yields obtained on oxidation of a secondary hydroxyl group to a carbonyl group in suitably protected sugars. The application of these new oxidants in the carbohydrate field is briefly surveyed. The product ketones are convenient intermediates for syntheses of amino, branched‐chain, deoxy, and other rare sugars. Some representative syntheses are ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Reviews (46,54,55) list little reported information on use of strong bases (e.g., potassium-ter£-butoxide, sodium acetate) in oxidations with methyl sulfoxide; however, sodium bicarbonate was used as an acid acceptor in the oxidation of aromatic halides or tosylates (46). The procedure below describes the use of a mixture of methyl sulfoxide, acetic anhydride and potassium terf-butoxide for acetylation of a sugar or inosose phenyl hydrazone to yield a ^-elimination product.…”
Section: Methodsmentioning
confidence: 99%
“…Reviews (46,54,55) list little reported information on use of strong bases (e.g., potassium-ter£-butoxide, sodium acetate) in oxidations with methyl sulfoxide; however, sodium bicarbonate was used as an acid acceptor in the oxidation of aromatic halides or tosylates (46). The procedure below describes the use of a mixture of methyl sulfoxide, acetic anhydride and potassium terf-butoxide for acetylation of a sugar or inosose phenyl hydrazone to yield a ^-elimination product.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that carbohydrate molecules possessing the enone functionality are the preferred precursors for the synthesis of branched-chain and rare sugars. [17][18][19][20][21][22] However enones are key intermediates in the synthesis of monosaccharides from non-carbohydrate precursors. 23 The stereochemical relationships at C-2, C-3 and C-4 are determined by a wise choice of reaction sequences: reduction of ketone and cishydroxylation or epoxidation.…”
Section: Anmentioning
confidence: 99%
“…109 Os cetoaçúcares α,β-insaturados são excelentes materiais de partida para a síntese de aminoaçúcares. 110 Em 1982, Holder 111 fez uma revisão destas hexenopiranosiduloses.…”
Section: Síntese De Aminoaçúcares De Cadeia Ramificada a Partir De Ceunclassified